2014
DOI: 10.1002/jor.22735
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone 1–34 enhances extracellular matrix deposition and organization during flexor tendon repair

Abstract: Purpose Parathyroid hormone (PTH) 1-34 is known to enhance fracture healing. Tendon repair is analogous to bone healing in its dependence on the proliferation and differentiation of mesenchymal stem cells, matrix formation, and tissue remodeling.1-3 We hypothesized that PTH 1-34 enhances tendon healing in a flexor digitorum longus (FDL) tendon repair model. Methods C57Bl/6J mice were treated with either intraperitoneal PTH 1-34 or vehicle-control (PBS). Tendons were harvested at 3-28 days for histology, gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
0
18
0
1
Order By: Relevance
“…PTH (40 mg/kg) was therefore administered, by either subcutaneous or intraperitoneal injections. In comparison to controls, PTH promoted an early formation of reparative tissue associated with an increased expression of extracellular matrix genes, including fibrillar collagens, type I and type III, and fibronectin 47 . Similarly to previous experiments, no significant differences in tensile strength were seen.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…PTH (40 mg/kg) was therefore administered, by either subcutaneous or intraperitoneal injections. In comparison to controls, PTH promoted an early formation of reparative tissue associated with an increased expression of extracellular matrix genes, including fibrillar collagens, type I and type III, and fibronectin 47 . Similarly to previous experiments, no significant differences in tensile strength were seen.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…This model has been used to assess knock-out mouse models 13,14 , and to test different pharmacological approaches to improve healing 1518 . Histological analyses of this model, using immunohistochemistry and in situ hybridization, can provide important insights in to the localization of key genes and proteins during healing.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, PTH treatment reduced the expression of the chondrocytic genes aggrecan and sox9, suggesting that it may also help in the maintenance of a tenocytic lineage. The clinical correlation between high serum PTH and poor tendon health is likely due to continuous exposure to PTH and increased bone resorbing osteoclast activity at the tendon-bone interface 14,15 , rather than the short or intermittent administration discussed in this paper and the pre-clinical studies published to date [7][8][9] . These results suggest that PTH may have a slight beneficial effect on tendon healing, particularly in the tendon-bone area as pre-clinical studies have suggested.…”
Section: Discussionmentioning
confidence: 89%
“…However, when taken into context with previously published data, it may have a use in treating tendonbone defects, where tendon, fibrocartilage and bone occur within millimetres. Clinically, hypothyroidism has been linked to musculoskeletal problems in humans 12 , and increased serum PTH is associated with tendon laxity and spontaneous tendon rupture [13][14][15] , although pre-clinical in vivo studies using PTH suggest it may have some benefit in tendon healing [7][8][9] . In our study PTH had no effect on tendon proliferation or collagen production, but did increase the expression of decorin, which plays a role in matrix assembly and could have direct implications on collagen fibrillogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation